Expression of AtLEC2 and AtIPTs promotes embryogenic callus formation and shoot regeneration in tobacco - Li, Ke (BMC Plant Biol, 2019)
BACKGROUND: LEAFY COTYLEDON 2 (LEC2) acts throughout embryo morphogenesis and maturation phase to maintain embryogenic identity. Our previous study stated that Arabidopsis thaliana LEC2 (AtLEC2) driven by glucocorticoid receptor-dexamethasone (GR-DEX) inducible system (AtLEC2-GR) triggers embryogenic callus formation in tobacco (Nicotiana tabacum). RESULTS: In this study, the adenosine phosphate isopentenyltransferase genes AtIPT3, AtIPT7 and the tRNA isopentenyltransferase gene AtIPT9 were overexpressed in the AtLEC2-GR transgenic background. In the AtIPT7-OE AtLEC2-GR and AtIPT9-OE AtLEC2-GR seedlings, high-quality embryogenic callus was obtained under the DEX condition, and the shoot regeneration efficiency was 2 to 3.5 folds higher than AtLEC2-GR alone on hormone free medium without DEX. Transcriptome analyses showed that up-regulated BBM, L1L, ABI3, and FUS3 might function during embryogenic callus formation. However, at the shoot regeneration stage, BBM, L1L, ABI3, and FUS3 were down-regulated and Type-B ARRs were up-regulated, which might contribute to the increased shoot regeneration rate. CONCLUSIONS: A novel system for inducing shoot regeneration in tobacco has been developed using the GR-DEX system. Induced expression of AtLEC2 triggers embryogenic callus formation and overexpression of AtIPT7 or AtIPT9 improves shoot regeneration without exogenous cytokinin. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12870-019-1907-7) contains supplementary material, which is available to authorized users.